Conceptual issues of internal financial control in corporations - N. V. Zhuravleva; T. E. Karmanova; E. N. Podshivalova (Путеводитель предпринимателя)
The article describes methods of financial control within the corporate principles and classification of internal financial controls. The features of the specifics of internal corporate financial control by studying the characteristics of corporate governance and corporate control.